Fibroblast growth factor-21: Preserving cell viability in diabetic neuropathy through the AKT/PI3K cellular pathway - Orhan, Seval Ülkü; Bulut, Ferah; Tekin, Suat; Ozcan, Mete (My University, 2024)
Aim: This study aims to investigate the potential neuroprotective effects of fibroblast growth factor-21 (FGF21) on dorsal root ganglion (DRG) neurons under high glucose (HG) conditions, mimicking diabetic neuropathy. Specifically, we hypothesize that FGF21 enhances cell viability and reduces glucose-induced neuronal death via the activation of the phosphatidyl-inositol-3-kinase (PI3K)/AKT signaling pathway. Materials and Methods: DRG neurons were cultured from 1-day-old to 2-day-old Wistar rats and exposed to HG concentrations to simulate diabetic conditions. Various concentrations of FGF21 were administered to the DRG neurons. Cell viability was assessed using the MTT assay (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide), a widely used enzymatic method for determining cellular metabolic activity. The involvement of the PI3K/AKT signaling pathway in mediating the effects of FGF21 was also examined through biochemical assays and pathway inhibitors. Results: Administration of FGF21 to DRG neurons exposed to HG conditions significantly protected cell viability and reduced glucose-induced neuronal death (p<0.05). The protective effects of FGF21 were found to be dose-dependent, with higher concentrations showing more pronounced benefits. Furthermore, the activation of the PI3K/AKT signaling pathway was confirmed to play a crucial role in the neuroprotective mechanism of FGF21, as inhibition of this pathway attenuated the protective effects. Conclusion: This study demonstrates for the first time that FGF21 has a neuroprotective effect on DRG neuron survival in a diabetic neuropathy model. By activating the PI3K/AKT signaling pathway, FGF21 helps maintain cell viability and reduces glucoserelated neuronal death. These findings provide a promising basis for the development of new therapeutic strategies for the treatment of diabetic neuropathy, leveraging the neuroprotective properties of FGF21.
Keywords: Cell viability; Dorsal root ganglion; Diabetic neuropathy; Fibroblast growth factor-21; In vitro model